2020
DOI: 10.1158/1535-7163.mct-20-0095
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Androgen Receptor Governs Radiation Resistance in a Subset of Glioblastomas Vulnerable to Antiandrogen Therapy

Abstract: ◥New approaches are needed to overcome intrinsic therapy resistance in glioblastoma (GBM). Because GBMs exhibit sexual dimorphism and are reported to express steroid hormone receptors, we reasoned that signaling through the androgen receptor (AR) could mediate therapy resistance in GBM, much as it does in AR-positive prostate and breast cancers. We found that nearly half of GBM cell lines, patient-derived xenografts (PDX), and human tumors expressed AR at the transcript and protein level-with expression levels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
7
19
1
Order By: Relevance
“…However, there is much less information available in brain tumors for steroid hormone receptor expressions or response to hormonal-particularly androgensuppression. Previous studies, as well as our own, showed that androgen receptors were consistently detected in a higher proportion of gliomas (17,27,28,31). These findings may help to explain the gender difference in GBM incidence and indicate that AR might be a promising therapeutic target for treating GBM.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, there is much less information available in brain tumors for steroid hormone receptor expressions or response to hormonal-particularly androgensuppression. Previous studies, as well as our own, showed that androgen receptors were consistently detected in a higher proportion of gliomas (17,27,28,31). These findings may help to explain the gender difference in GBM incidence and indicate that AR might be a promising therapeutic target for treating GBM.…”
Section: Discussionsupporting
confidence: 72%
“…It is also noted that the survival curve after enzalutamide treatment showed initially the same pattern as control group but separated eventually indicating a heterogeneity of tumor response to the drug. Our pre-clinical results indicate that likely further dose escalation study for GBM patients or combining this drug with other standard care modalities for GBM such as temozolomide and/or RT may be necessary to further improve the outcome, as supported by the most recently published data from Werner et al in the flank implant tumor model (31).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Werner and cols determined that AR expression at the transcript and protein levels in LN18, T98G glioblastoma cell lines, patient-derived xenografts (PDX), and human tumors overlapped with the expression of this receptor in primary prostate cancer. These authors also found that anti-androgens' treatment slowed the growth and increased sensitivity to radiation of LN18, T98G, and U87 cell lines and patient-derived xenografts (in vitro and in vivo) [111]. These results suggest that T is involved in the growth of these tumors, regardless of the tumors' grade, in the progression toward a more proliferative, migratory, and invasive state (see Fig.…”
Section: Gonadal Steroid Hormones In Prevalence and Progression In Glioblastoma: Tmentioning
confidence: 80%
“…There is no sudden increase in the incidence of gliomas during and after puberty (83) and data on the increased risk of glioma due to exposure to exogenous hormones are inconclusive, although they tend to lean towards protective properties of estrogens (84). However, in vitro and in vivo studies indicate that by affecting signaling pathways of sex hormones, we may be able to modulate response to radio-and chemotherapy (85,86). Zhou et al showed that GBM cells overexpressing estrogen receptor β were sensitized to TMZ treatment (85), and Werner et al reported that inhibition of the AR sensitizes GBM cells to radiotherapy (86).…”
Section: Sex Hormonesmentioning
confidence: 99%